Conceptual differentiation, integration and empathic prediction - Neimeyer, Robert A.; Neimeyer, Greg J.; Landfield, A. W. (Journal of personality, 1983)
Several investigators have examined the relationship of a rater's cognitive complexity to accurate empathic prediction of a target's self‐concept or behavior, with mixed results. The present study sought to clarify this relation by considering both the conceptual differentiation (functionally independent construction) and integration (ordination) of both rater and target as they bear on predictive accuracy at early and later stages of acquaintance. Two sets of ten subjects participated in weekly self‐disclosure groups, and attempted to predict one another's self‐ratings on personal constructs after four and eighteen weeks of structured dyadic interaction. Results suggested that (a) the conceptual structure of the rater was unrelated to predictive accuracy, (b) high differentiated/low integrated targets were less accurately predicted at Time 1, (c) raters generally became more accurate predictors over time, and (d) conceptual structure was related to predictive accuracy at early, but not advanced stages of relationship. These findings were interpreted within an expanded theoretical framework emphasizing the multidimensional assessment of cognitive complexity as well as the stage of acquaintance at which social prediction takes place.